ANTIMICROBIAL ACTIVITY OF OZONE, LOW POWER LASER AND LASER-OZONE ASSOCIATION AGAINST CULTURES OF ORAL BACTERIA FROM CAPTIVE BIG CATS - Ferreira, Jair Camargo; de Sousa, Yoshihara Cristina; Barros, Renata Alves; Ferreira, Cristiane Marissa Piacitelli Prado; Ambrósio, Maria Anita Lemos Vasconcelos; Ambrósio, Sérgio Ricardo; Dias, Fernanda Gosuen Gonçalves; Paulino, Daniel; Rodrigues, Marcela Aldrovani (Seven Editora, 2025)
The goal of the present study was to characterize the antimicrobial and antibiofilm potential of laser therapy, ozone therapy (gas, water and oil presentations), and photo-ozone therapy against bacteria isolated from the oral cavity of captive felines: Puma concolor (n=4), Panthera onca (n=1), and Panthera leo (n=1). The minimum inhibitory and bactericidal concentrations (MIC and CMB, respectively) of the treatments were determined against the planktonic form of the following pathogens: Enterococcus faecalis, Leifsonia aquatica, Oerskovia sp., Serratia marcescens, Corynebacterium sp., Providencia pustigianii and P. rustigianii. The antibiofilm action of a treatment was evaluated whenever the respective therapy was effective in inactivating the planktonic form of the pathogens. Water ozonation (bubbling 500 mL of solvent with 70 μg O3 mL-1 and 125 mL min-1 for 7 minutes) was performed immediately before treatments. The ozonated sunflower oil had a peroxide value >600 mmol-equiv. kg-1. Therapies with O3 gas (70 μg O3 mL-1 and 125 mL min-1) and low-intensity laser (660 nm and 80 J cm2) were performed for 120 and 160 seconds, respectively. Photo-ozone therapy used low-intensity laser and O3 gas sequentially. Regardless of the pathogen, the MIC and MBC of ozonated water, ozonated sunflower oil, and O3 gas against free bacteria were similar to those of their controls. Similarly, both laser therapy and photo-ozone therapy showed MIC and MBC >100%. In contrast, the MIC and MBC of ozonated sunflower oil (0.062 to 40%) and chlorhexidine digluconate (0.46 to 3.69 µg mL-1) confirmed the bactericidal action of both against free bacteria. When evaluated against biofilms, the MIC and MBC of ozonated sunflower oil varied between 10 and 60% depending on the pathogen. Under the conditions, only ozonated sunflower oil with a high peroxide index showed germicidal and antibiofilm activity against oral bacteria of captive large cats. DOI: https://doi.org/10.56238/sevened2025.029-105